2010
DOI: 10.1097/prs.0b013e3181ef8ea3
|View full text |Cite
|
Sign up to set email alerts
|

Refining Outcomes in Dorsal Hand Coverage: Consideration of Aesthetics and Donor-Site Morbidity

Abstract: The aesthetic outcome of dorsal hand reconstruction is dependent on flap choice, with statistically significant differences in revision surgeries and aesthetics among flap types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 21 publications
1
42
2
4
Order By: Relevance
“…that were used to cover dorsal hand defects (Level of Evidence: Therapeutic, III) . 63 Evaluated measures included; flap survival, donor-site morbidity and the need for debulking procedures. In addition, a panel of plastic surgeons and non-physician aestheticians subjectively analyzed the final appearance of the flaps.…”
Section: Dorsum Of the Handmentioning
confidence: 99%
“…that were used to cover dorsal hand defects (Level of Evidence: Therapeutic, III) . 63 Evaluated measures included; flap survival, donor-site morbidity and the need for debulking procedures. In addition, a panel of plastic surgeons and non-physician aestheticians subjectively analyzed the final appearance of the flaps.…”
Section: Dorsum Of the Handmentioning
confidence: 99%
“…Even radial forearm flaps, which have characteristically less bulk, underwent debulking in 62% of cases. 33 …”
Section: Discussionmentioning
confidence: 97%
“…With current high rates of obesity, large body habitus results in thick fasciocutaneous flaps, which may necessitate considerable debulking. A recent study by Parrett et al 33 found that 88% of ALT flaps utilized required an average of 2 debulking procedures per flap. Even radial forearm flaps, which have characteristically less bulk, underwent debulking in 62% of cases.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, flap survival should no longer be the only goalVbulky flaps are not only unsightly but can also limit function if not serially debulked. 4 Because the dorsal finger is cosmetically more unique and important than the dorsal hand, flap choice and outcomes should take into account the final aesthetics of the reconstruction and its match to normal dorsal finger skin; this has not been studied in a large comparative series of flaps. Similarly, outcome should also focus on the secondary interventions needed to achieve the final result such as DB and/or flap separation procedure in multiple dorsal finger defects and the resulting donor-site morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, these injuries are managed with primary soft tissue coverage followed by a later secondary tendon reconstruction. 3 In literature, local or regional flaps are often the preferred choice for soft tissue reconstruction of hand and digits 4 ; however, when facing larger dorsal defects, extensive and multiple digits injuries, these flaps are sometimes precluded and free flaps are frequently considered as the optimal options. 5 Free arterialized venous flaps (AVFs) with the advantages of thin, pliable, easy to elevate, and minimal donor-site morbidity have gained special popularity in the reconstruction of the dorsal finger defects despite of the concerns of inconsistent survival status.…”
mentioning
confidence: 99%